Length of Utterance, in Morphemes or in Words?: MLU3-w, a Reliable Measure of Language Development in Early Basque - Ezeizabarrena, Maria-José; Garcia Fernandez, Iñaki (Frontiers in Psychology, 2018)
The mean length of utterace (MLU), which was proposed by Brown (1973) as a better index for language development in children than age, has been regularly reported in case studies as well as in cross-sectional studies on early spontaneous language production. Despite the reliability of MLU as a measure of (morpho-)syntactic development having been called into question, its extensive use in language acquisition studies highlights its utility not only for intra- and inter-individual comparison in monolingual language acquisition, but also for cross-linguistic assessment and comparison of bilinguals’ early language development (Müller 1993; Yip and Mathews, 2006; Meisel 2011). An additional issue concerns whether MLU should be measured in words (MLU-w) or morphemes (MLU-m), the latter option being the most difficult to gauge, since new challenges have arisen regarding how to count zero morphemes, suppletive and fused morphemes. The different criteria have consequences, especially when comparing development in languages with diverging morphological complexity. A variant of MLU, the MLU3, which is calculated out of the three longest sentences produced (MLU3-w and MLU3-m), is included among the subscales of expressive language development in CDI parental reports (Fenson et al., 1993, 2007). The aim of the study is to investigate the consistency and utility of MLU3-w and MLU3-m as a measure for (morpho-)syntactic development in Basque, an agglutinative language. To that end, cross-sectional data was obtained using either the Basque CDI-2 instrument (16- to 30-month-olds) or the Basque CDI-3 (30- to 50-month-olds). The results of analysing reports on over 1200 children show three main findings. First, MLU3-w and MLU3-m can report equally well on very young children’s development. Second, the strong correlations found between MLU3 and expressive vocabulary in the Basque CDI-2 and CDI-3 instruments, as well as between MLU3 and both nominal and verbal morphology scales, confirm the consistency not only of MLU3 but also of the two Basque CDI instruments. Finally, both MLU3-w and MLU3-m subscales appear sensitive to input after age 2, which emphasises their utility for identifying developmental patterns in Basque bilinguals.